Hakikat Ibadah di Bulan Ramadhan - Abdul Rahman; Devi Putri Ramadani; Riska Widya Hakim (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2023)
Ibadat Or Worship Is A Word Taken From The Arabic Word 'Ibadah (عبادة). In Indonesian Terminology As Found In The Big Indonesian Dictionary (KBBI), This Word Has The Meaning: An Act Or Expression Of Devotion To Allah Or God Based On Religious Regulations. The Essence Of The Meaning Of Fasting Is Not Only Being Able To Refrain From Eating, Drinking Or Having Sex. During The Day Of Ramadan (Jimak). More Than That, The Meaning Of Fasting Is To Refrain From All Actions And Words That Are Forbidden. In This Sense, It Is Important For People When Fasting, Not Only To Be Able To Restrain Thirst And Hunger, But Also To Be Able To Restrain Their Mouth, Eyes, Ears, Hands And Other Parts Of The Body From Actions That Can Reduce Or Eliminate The Rewards Of Fasting. رُبَّ صَائِمٍ حَظُّهُ مِنْ صِيَامِهِ الجُوْعُ وَالعَطَشُ "How Many People Fast But They Get Nothing From Their Fast Except Hunger And Thirst." (HR Ath Thabaroni).